TNA: value creation in competency-based training of teaching and learning / Prof. Dr. Mohd Mustafa Mohd Ghazali, Prof. Dr. Zubaidah Zainal Abidin and Associate Prof. Posiah Mohd Isa - Mohd Ghazali, Prof. Dr. Mohd Mustafa; Zainal Abidin, Prof. Dr. Zubaidah; Mohd Isa, Associate Prof. Posiah (Research Management Institute (RMI), 2011)
Very often academicians' needs for training are given the least priorities in the human resource training and development of any institutions of higher learning in Malaysia. In the era of globalization, graduates must be equipped with the necessary knowledge and skills in order to meet the challenges of borderless corporate environment. Academicians are responsible in grooming the students with the relevant tools to be at competitive edge. Yet academicians are not exposed or given the opportunity to upkeep themselves with the necessary information or guidance which can be used in the process of delivering lectures to the students. This study explores the training needs and opportunities among lecturers in UiTM and its association with the lecturers' competency level. Results from this study could provide a platform for staff's training and development and assist in planning, organizing and implementing future training programme.